1999
DOI: 10.1021/ic990588e
|View full text |Cite
|
Sign up to set email alerts
|

Phenylethynyl Substituent Effects on the Photophysics and Electrochemistry of [Cu(dpp)2]+ (dpp = 2,9-Diphenyl-1,10-phenanthroline)

Abstract: The syntheses, absorption spectra, emission spectra, electrochemical behavior, and excited-state lifetimes of a series of phenylethynyl-substituted copper(I) complexes are reported. These results are compared to those of the parent complex, [Cu(dpp)2]+ (dpp = 2,9-diphenyl-1,10-phenanthroline), to explore the effects of extended electronic delocalization on the photophysics of luminescent copper(I) bis(phenanthroline) complexes. Visible excitation of these complexes leads to emission from metal-to-ligand charge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
0
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 41 publications
3
76
0
3
Order By: Relevance
“…In particular, the redox potential becomes more positive when the steric constraint in the 2-and 9-positions increases, as this can prevent the rearrangement of the coordination sphere to the favored square-planar for the oxidized Cu II species and thus stabilize the Cu I state. [14,33,34] A comparison of the complexes studied here revealed a complete agreement with this trend: increasing the 2,9-substituents on 1,10-phenanthroline from diphenyl (complexes 7, 10) to phenyl/naphthyl (8,11), and then to dinaphthyl (9,12) shifted the [CuL 2 ] 2+/+ couple to more positive potentials (Figure 6a,b (Table 2). For the complexes with the CuCl 2 -anion, 7-9, there is also an irreversible reduction peak at 0.2-0.3 V, which might be caused by the dissociation or ligand exchange during the redox process.…”
Section: Electrochemical Propertiessupporting
confidence: 76%
See 1 more Smart Citation
“…In particular, the redox potential becomes more positive when the steric constraint in the 2-and 9-positions increases, as this can prevent the rearrangement of the coordination sphere to the favored square-planar for the oxidized Cu II species and thus stabilize the Cu I state. [14,33,34] A comparison of the complexes studied here revealed a complete agreement with this trend: increasing the 2,9-substituents on 1,10-phenanthroline from diphenyl (complexes 7, 10) to phenyl/naphthyl (8,11), and then to dinaphthyl (9,12) shifted the [CuL 2 ] 2+/+ couple to more positive potentials (Figure 6a,b (Table 2). For the complexes with the CuCl 2 -anion, 7-9, there is also an irreversible reduction peak at 0.2-0.3 V, which might be caused by the dissociation or ligand exchange during the redox process.…”
Section: Electrochemical Propertiessupporting
confidence: 76%
“…Cu I complexes 7-12 undergo a reversible (for 7 and 10) or quasireversible (for 8, 9, 11, and 12) one-electron oxidation process at 0.90-1.06 V as a result of the Cu II /Cu I couple (Figure 6a,b), which is similar to many (phenanthroline)copper complexes. [4,31,34,37] The peaks for complexes 8 and 9 show a slight split with a shoulder. It has been reported that the Cu II /Cu I couple of [Cu(NN) 2 ] n+ complexes depends largely on the nature of the substituents on the phenanthroline.…”
Section: Electrochemical Propertiesmentioning
confidence: 99%
“…Some issues have been addressed by the incorporation of bulky substituents into 2 and 9 positions of the phen-based ligands, to preclude the exciplex formation thus, elongating the lifetime of their excited states and increasing their quantum yields [25,26,[108][109][110][111][112][113]. However, the most significant impact on the photophysical properties of these [Cu(NˆN) 2 ] + systems was achieved by the inclusion of phosphine ligands by McMillin and coworkers [44,45].…”
Section: Heteroleptic Diimine/diphosphine [Cu(nˆn)(pˆp)] + Complexesmentioning
confidence: 99%
“…It has been shown that the presence of bulky groups at 2,9 positions can block solvent access to the Cu center to prevent the formation of an "exciplex", lowering the energy gap between the MLCT and the ground states and accelerating the ground state recovery, and thus result in a longer MLCT lifetime and a higher emission quantum yield. 14,15,18,[26][27][28][29] These studies suggest that the excited state dynamics of Cu I diimine complexes could be controlled by the dihedral angle between the two phenanthroline ligand planes as well as the solvent accessibility to the Cu center. Previously, we have investigated the structural influence on the excited state dynamics in an extreme case of a completely locked tetrahedral coordination geometry due to the stericallybulky t-butyl groups in bis(2,9-di-tert-butyl-1,10-phenanthroline)- 19 We showed that [Cu…”
mentioning
confidence: 93%